METHODOLOGY OF DIRECTING STUDENTS TO PROFESSIONS THROUGH ENTREPRENEURSHIP IN TECHNOLOGY CLASSES - Marufjonov Okhunjon (Journals Park Publishing, 2024)
President of the Republic of Uzbekistan Sh . In the words of Mirziyoyev, "To develop our youth into people who think independently, have high intellectual and spiritual potential, and who are not inferior to their peers in any field on the world scale, our state and society have to be happy strength and opportunities mobile we deliver”; that they insist is a sign of concern for the future of young people.